2005
DOI: 10.1039/b419425j
|View full text |Cite
|
Sign up to set email alerts
|

In situ hybridization of PNA/DNA studied label-free by electrochemical impedance spectroscopy

Abstract: The in situ hybridization kinetics of label-free DNA on mixed monolayers of peptide nucleic acid (PNA) and 6-mercapto-1-hexanol (MCH) on Au electrodes was investigated by electrochemical impedance spectroscopy (EIS) and used to discriminate the fully complementary DNA from the single-base mismatched hybrids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 21 publications
1
65
1
Order By: Relevance
“…It is also possible that the relationship between target coverage and impedance response ΔZ(θ) is logarithmic, as is the case with most field-effect biosensors [153]. Some authors (e.g., [154,155]) have obtained good fits of experimental data with the Langmuir isotherm, and there has been at least one report of sensor response being exponential in target concentration [156]. One complicating factor is whether the binding is controlled kinetically or reaches equilibrium during the experiment.…”
Section: Response Curvementioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the relationship between target coverage and impedance response ΔZ(θ) is logarithmic, as is the case with most field-effect biosensors [153]. Some authors (e.g., [154,155]) have obtained good fits of experimental data with the Langmuir isotherm, and there has been at least one report of sensor response being exponential in target concentration [156]. One complicating factor is whether the binding is controlled kinetically or reaches equilibrium during the experiment.…”
Section: Response Curvementioning
confidence: 99%
“…Liu et al reported a DNA sensor based on faradaic impedance spectroscopy and were able to easily detect 1 nM of 15mer target [155].The observed change in R ct is presumably due to electrostatic repulsion between the negatively-charged redox species and negative charge on the DNA. Probes were made of PNA, a DNA mimic with a neutral backbone, to increase fractional R ct change.…”
Section: Faradaic Studiesmentioning
confidence: 99%
“…Moreover, the exact association (hybridisation) and dissociation rate constants can be obtained. Thus, the method is comparable to a fluorescence technique (Liu et al, 2005). Monolayers of cysteine-linked peptide nucleic acid assembled on gold electrodes, were investigated for the sensing of DNA recognition (Degefa et al, 2008).…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…Liu et al have studied in situ hybridisation kinetic studies with label-free DNA target oligonucleotides on a mixed monolayer of PNA and mercaptohexanol on Au electrodes using EIS. EIS can be used to follow the in-situ hybridisation kinetics of PNA/DNA by recording the change of R ct with time (Liu et al, 2005). The immobilised PNA probes on the sensor surface are uncharged, and hence, do not affect the charge transfer from the redox indicator Fe(CN) 6 3-/4-to the electrode.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
See 1 more Smart Citation